2009
DOI: 10.2353/ajpath.2009.081154
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function FERMT1 Mutations in Kindler Syndrome Implicate a Role for Fermitin Family Homolog-1 in Integrin Activation

Abstract: Kindler syndrome is an autosomal recessive disorder characterized by skin atrophy and blistering. It results from loss-of-function mutations in the FERMT1 gene encoding the focal adhesion protein, fermitin family homolog-1. How and why deficiency of fermitin family homolog-1 results in skin atrophy and blistering are unclear. In this study, we investigated the epidermal basement membrane and keratinocyte biology abnormalities in Kindler syndrome. We identified altered distribution of several basement membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 55 publications
0
30
1
Order By: Relevance
“…The first symptoms of KS manifest during infancy and are characterized by trauma-induced skin blistering, which is due to the impaired integrin function in basal keratinocytes (Fassihi et al, 2005;Lai-Cheong et al, 2009;Penagos et al, 2004) (Fig. 2A).…”
Section: Subcellular Localisations Of Kindlinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first symptoms of KS manifest during infancy and are characterized by trauma-induced skin blistering, which is due to the impaired integrin function in basal keratinocytes (Fassihi et al, 2005;Lai-Cheong et al, 2009;Penagos et al, 2004) (Fig. 2A).…”
Section: Subcellular Localisations Of Kindlinsmentioning
confidence: 99%
“…Intriguingly, colony-forming efficiency assays of serially cultured primary keratinocytes that had been isolated from KS patients indicated accelerated depletion and premature senescence of SCs, suggesting that, similar to those mice that lack kindlin-1 in keratinocytes (Rognoni et al, 2014), the enhanced SC proliferation eventually leads to SC exhaustion, which is accompanied by a loss of SC-marker expression in the patient skin (Lai-Cheong et al, 2009;Piccinni et al, 2013). Two main defects have been identified in the KS mouse model that contribute to the hyperproliferation of Box 1.…”
Section: Subcellular Localisations Of Kindlinsmentioning
confidence: 99%
“…5a). Total and activated b1 integrin was assessed as described previously [9]. Total surface b1 integrin detected by the mouse monoclonal anti-b1 integrin Ab (4B7R) was similar in the cells transfected with KIND1wt (Fig.…”
Section: Exon 8-skipped Truncated Kindlin-1 In Vitromentioning
confidence: 99%
“…The KIND1 gene is the human homolog of the Caenorhabditis elegans gene, unc-112, which encodes a membrane-associated structural/signaling protein that has been implicated in linking the actin cytoskeleton to the extracellular matrix (ECM) [7,8]. Kindlin-1 deficiency is associated with cutaneous basement membrane zone abnormalities and reduced integrin activation [9]. Also, kindlin-1 is necessary for lamellipodia formation in vitro, which is mediated by RhoGTPase signaling [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that kindlin-1 overexpression in keratinocytes obtained from Kindler syndrome patients restores the normal cellular phenotype by enhancing integrin activation (Lai-Cheong et al, 2009). We therefore examined the effects of kindlin expression on integrin activation and signaling in cultured adult sensory neurons.…”
Section: Kindlin-1 But Not Kindlin-2 Overexpression Enhances Integrmentioning
confidence: 99%